(untitled) (Physical Education, Health and Social Sciences, 2025)
The purpose of the present study was to examine the emotional intelligence (EI) of educational leaders in government secondary schools in the District of Sialkot. Emotional intelligence is identified as one of the factors that affect successful leadership, decision-making, interaction, and the general school climate. This study adopted a descriptive research design and focused on all educational heads in the Tehsil secondary schools of Daska. Eighty-six schools, which included 86 educational leaders, were selected through a proportional stratified random sampling method. The Genos Emotional Intelligence Inventory (Genos EII), a self-report measure with a high degree of reliability and validity, was used to collect data: The Genos EII measures seven dimensions of EI, emotional self-awareness, emotional expression, emotional awareness of others, emotional reasoning, emotional self-management, emotional management of others, emotional self-control. One-sample t-tests were implemented to compare the means of educational leaders with the neutral scale value of 3. The results indicated that educational leaders scored well above the neutral mean on all dimensions of emotional intelligence with emotional reasoning showing the highest mean score. Male and female leaders showed that emotional awareness and regulation, as well as the ability to manage the emotions of other individuals, are high, which is a sign of strong interpersonal and leadership skills. The outcomes indicate that educational leaders with high levels of emotional intelligence can lead to effective leadership, stronger teacher-student relationship, and positive school climate. The paper highlights the need to incorporate emotional intelligence development programs into leadership training and professional development programs in schools.